In situ electrochemical-transmission surface plasmon resonance spectroscopy for poly(pyrrole-3-carboxylic acid) thin-film-based biosensor applications - Janmanee R. (2014)
In this study, we describe the combination of transmission surface plasmon resonance (TSPR) and electrochemical techniques for the application to biosensors with conducting polymers. Electropolymerization was employed to construct poly(pyrrole-3-carboxylic acid) (PP3C) film on a gold-coated grating substrate using pyrrole-3-carboxylic acid (P3C) monomer solution in 0.5 M H 2SO 4. In situ electrochemical-transmission surface plasmon resonance (EC-TSPR) measurements were carried out to study the kinetic and electroactivity properties of PP3C film. Immobilization of antihuman IgG on the activated surface and the binding process of human IgG and antihuman IgG in neutral solution could be detected in situ by EC-TSPR measurement. The surface modification steps on the PP3C layer led to an increase in intensity of the transmission peak. The performance, sensitivity, and utility of EC-TSPR spectroscopy showed obvious advantages for the detection of binding process with the simple experimental setup, and could be applied to the study of biomolecular interactions in various systems. © 2012 American Chemical Society.